Relevansi Konsep Nafkah dalam Hukum Keluarga Islam terhadap Dinamika Kehidupan Modern - Toha Ma'arif (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
The rapid development of modern life has brought significant changes to family structures, economic patterns, and gender roles. These transformations have created new challenges in the implementation of the concept of nafkah (financial support) in Islamic family law, particularly in balancing traditional obligations with contemporary realities. This study is motivated by the growing number of divorce cases in Islamic courts that are often linked to the husband’s negligence in fulfilling nafkah, as well as the shifting of economic responsibilities within households where wives increasingly contribute to family income. The primary aim of this research is to analyze the relevance of the nafkah obligation in Islamic family law to the dynamics of modern life, while also exploring the possibility of reinterpretation to ensure its alignment with the enduring principles of sharia. The study employs a library research method, drawing on primary sources such as the Qur’an, Hadith, classical fiqh literature, and the Compilation of Islamic Law, complemented by secondary sources including books, scholarly articles, and contemporary research findings. The results reveal that the concept of nafkah demonstrates flexibility and adaptability when viewed through the frameworks of maqāṣid al-sharī‘ah, responsive law theory, and gender justice. Thus, nafkah remains relevant in addressing modern needs like education, healthcare, and technology, while promoting cooperative roles between spouses. Keywords: Islamic family law, nafkah, maqāṣid al-sharī‘ah, gender justice, responsive law